Correlation of knowledge, dietary, and caries prevention behavior with dental caries experience among adolescents: a cross-sectional study - Subagio, Jessica Juliana; Suryanti, Netty; Setiawan, Asty Samiaty; Andiesta, Niekla Survia (Padjadjaran Journal of Dentistry, 2026)
Introduction: Adolescents are a high-risk group for dental caries, influenced by changes in dietary patterns and inadequate oral hygiene practices. Most interventions focus solely on improving knowledge; empirical evidence linking knowledge about cariogenic foods to actual behaviors related to caries experiences in adolescents is still limited in Indonesia. This study aims to analyze the correlation between knowledge of cariogenic foods, dietary behavior, and caries prevention behavior and dental caries experience in adolescents. Methods: This study used a cross-sectional analytical method with a correlational approach, involving 149 students aged 15-18 years from Senior High School of Jatinangor, Sumedang, West Java, Indonesia. The sample was selected through simple random sampling. Data were collected using a newly developed questionnaire that had been tested for validity and reliability. The questionnaire consisted of 11 items each on knowledge of cariogenic foods and dietary behavior, and 13 items on caries prevention behavior (oral hygiene behavior index). Dental caries experience was measured using the DMF-T index. Data were analyzed using the Spearman Correlation test. Results: Regarding knowledge of cariogenic foods, the majority of adolescents, 73 (48.99%), were categorized as having good knowledge. For dietary behavior, 103 (69.13%) adolescents were in the moderate category, and for caries prevention behavior, 99 (66.44%) adolescents were also in the moderate category. The average DMF-T index score was 8.11. The analysis showed no significant relationship between knowledge of cariogenic foods and dental caries experience (p = 0.264, r = 0.179). However, there was a significant relationship between dietary behavior (p = 0.000, r = 0.696) and caries prevention behavior (p = 0.000, r = 0.582) with dental caries experience. Conclusion: Dietary and caries prevention behaviors correlate with caries experience. However, knowledge about cariogenic foods does not correlate with caries experience.